SNAKE DIVERSITY AND SURVEY BIAS IN WESTERN KAZAKHSTAN REVEALED BY OBSERVED AND MODELLED SPECIES RICHNESS - Mizsei, Edvárd (Вестник ЗКУ, 2025)
Understanding biodiversity patterns in under-surveyed regions is essential for effective conservation planning. Western Kazakhstan, despite its extensive steppe and semi-desert habitats, remains poorly documented in terms of reptile diversity. In this study, we compiled all available snake occurrence records from field surveys and online biodiversity repositories to provide the first integrated assessment of species richness and sampling bias across the region. We recorded 16 snake species from 1,143 observations, but the spatial distribution of records was highly uneven, with more than 80% of grid cells lacking any detections. As a result, observed richness was restricted to a small number of well-surveyed locations, creating a fragmented picture of regional diversity. To complement these patterns, we generated spatially explicit predictions of species richness using ensemble species distribution models for the best-represented taxa. Predicted richness revealed broad areas of environmental suitability, particularly in the northern parts of the region, extending far beyond the locations of known records. Observed and predicted richness were moderately correlated, yet both were significantly associated with sampling effort, indicating persistent data bias. By identifying environmentally suitable but poorly surveyed areas, our results provide clear priorities for future fieldwork and highlight substantial knowledge gaps in the herpetofauna of Western Kazakhstan.